N-unsubstituted Imidazoles: Design, Synthesis, and Antimicrobial Evaluation - Davood, Asghar; EbrahimiNassimi, Yassamin; Sardari, Soroush; Farahani, Yekta F. (Current Pharmaceutical Design, 2023)
Background: All the current antifungal azoles have one substituted nitrogen atom in their imidazole or triazole rings. In this study, eleven imine and amine derivatives of imidazole, in which both nitrogen atoms of the imidazole ring are unsubstituted, were designed and synthesized. Materials and Methods: Imine derivatives were prepared by condensation of imidazole-4-carboxaldehyde with appropriate amines, and then in the next step, using sodium borohydride, the imines were reduced to amine derivatives. Docking studies reveal unsubstituted nitrogen atom of the imidazole ring coordinated well with the heme molecule of the receptor. In vitro, antimicrobial evaluation was tested on Candida albicans, E. coli, and Staphylococcus aureus. Results: Based on the results of the antimicrobial study, compound 10, which contains 4-chlorobenzyl moiety, proved to be the most potent compound against Candida albicans, and it was more active than the reference drug fluconazole and showed comparable activity to amphotericin B. Compounds 10 and 11 and compounds 8, 10 and 11 showed significant responses against E. coli and Staphylococcus aureus respectively. Conclusion: It is concluded that compound 10 can be acted as a new lead compound to find new azoles antifungal.
Keywords: Imidazole-4-carboxaldehyde